2016
DOI: 10.1001/jamaophthalmol.2016.1669
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Aflibercept, Bevacizumab, and Ranibizumab for Diabetic Macular Edema Treatment

Abstract: Importance: Anti-vascular endothelial growth factor (anti-VEGF) medicines have revolutionized diabetic macular edema (DME) treatment. A recent randomized clinical trial comparing anti-VEGF agents for patients with decreased vision from DME found that at one year aflibercept (2.0-mg) achieved better visual outcomes than repackaged (compounded) bevacizumab (1.25-mg) or ranibizumab (0.3-mg); the worse the starting vision, the greater the treatment benefit with aflibercept. However, aflibercept and ranibizumab, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 18 publications
3
90
0
3
Order By: Relevance
“…Regarding cost, based on incremental cost-effectiveness ratios aflibercept and ranibizumab are not considered cost-effective by standard benchmarks (e.g., greater than $150,000 quality adjusted life years). 3 Although post-hoc analyses should be viewed with caution given the potential for bias, these results explore clinically relevant questions that give further information potentially helpful for interpreting DRCR.net Protocol T results through 2 years.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding cost, based on incremental cost-effectiveness ratios aflibercept and ranibizumab are not considered cost-effective by standard benchmarks (e.g., greater than $150,000 quality adjusted life years). 3 Although post-hoc analyses should be viewed with caution given the potential for bias, these results explore clinically relevant questions that give further information potentially helpful for interpreting DRCR.net Protocol T results through 2 years.…”
Section: Discussionmentioning
confidence: 94%
“…Typically, patients with retinal diseases such as DME require multiple doses of anti-VEGF agents. As the burden of injections is high in many of these retinal disorders, there are still some relevant questions about treatment, such as (1) the choice of agent and (2) the economic burden of therapy [28, 30]. In this regard, the use of corticosteroid implants may offer advantages, given the less frequent need for injections [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that the cost-effectiveness of aflibercept and ranibizumab for DME is poorer than that of bevacizumab [15]. In cases of refractory DME, frequent anti-VEGF antibodies injection may be required.…”
Section: Discussionmentioning
confidence: 99%